Creating pressurised training environments in elite sport - Stoker, M. (2017)
Pressure training (PT) is indicated to be an intervention for preventing self-focus and distraction methods of choking that could be more effective (Oudejans & Pijpers, 2010), ecological (cf. Lawrence et al., 2014), and popular (Bell, Hardy, & Beattie, 2013; Sarkar, Fletcher, & Brown, 2014) than more widely recognised approaches (Hill, Hanton, Matthews, & Fleming, 2010a) such as implicit (Mullen, Hardy, & Oldhan, 2007) and analogy learning (Masters, 2000). However, whilst research has exemplified stressors being used to create pressure (e.g., Lawrence et al., 2014) and provided extensive detail on methods that could be useful for conducting the preexposure stages of PT (e.g., Johnston & Cannon-Bowers, 1996), there was an absence of research investigating how to systematically create pressurised training environments in sport. This notion suggested that PT was being practiced in elite sport in the absence of comprehensive theoretical underpinnings. To address this, study one explored how 11 elite coaches systematically created and exposed athletes to PT environments. The emergent framework suggested that coaches manipulated two key areas: demands of training, which considered the nature of physical and cognitive demands directly related to a training exercise, and consequences of training, which concerned performance-contingent outcomes. Demands were organised via manipulating task, performer, and environmental stressors, and consequences were shaped using forfeit, reward, and judgment stressors. To test the efficacy of this framework, study two examined the effects of manipulating demands and consequences on experiences of pressure in elite Netball. To further extend knowledge, study three examined the impact of each individual demand (i.e., task, performer and environmental) and consequence (i.e., reward, forfeit and judgment) stressor on pressure in elite Disability Shooting. Study three`s results were synonymous with those of study two in indicating that perceived pressure only increased in conditions where consequences were introduced. This result suggested that these stressors were essential for increasing pressure. Moreover, study three indicated that the judgment stressor had the greatest influence of all stressors and, thus, presented coaches with the most effective means for maximising pressure. Across both studies, manipulating demands in isolation did not influence pressure in any condition. Yet, these stressors always negatively impacted performance. Hence, collectively the findings support and build on the framework by indicating that demands and consequences have distinct roles when PT; demand stressors could be critical for shaping performance whereas consequences appear essential for producing pressure. These findings have important applied implications. Firstly, previous research suggested that coaches may rely on demands, in place of consequences, to produce pressure (cf. Weinberg, Butt, & Culp, 2011). Secondly, literature has predominantly indicated consequences are important, but not essential, when creating pressure (e.g., Oudejans & Pijpers, 2009). Therefore, there may be a need to expand knowledge in applied and scientific arenas regarding the distinct roles of demands and consequences when PT. In light of these points, the present thesis contributes findings to underpin methods for systematically creating and exposing athletes to PT environments. These findings combine with previous literature relating to the pre-exposure stages of PT (e.g., Johnston & Cannon-Bowers, 1996) to enable the documentation of a more comprehensive account of how to perform all the stages involved in PT. Accordingly, an epilogue in chapter seven outlines such an account and serves as a guide for practitioners and coaches conducting PT.